Positive Fictional Authority Legislative Ratio in Government Administration Laws and Job Creation Laws - Mustapa, Iqbal; Abdussamad, Zamroni; Towadi, Mellisa (Universitas Negeri Gorontalo, 2022)
This study aims to determine the causes of the low fulfillment of wife and children's income after divorce and the efforts that can be made to optimize the fulfillment of wife and children's income, especially in divorce cases. The research method used is normative with a case approach (statute approach) and a conceptual approach. The results of the study show that the percentage of women's and children's rights in religious courts has a very low percentage, so it is necessary for judges to use their ex officio rights massively for the optimal fulfillment of women's and children's rights. In addition, the position of the SEMA which is considered to be a guideline or policy and does not have strong binding power, it is necessary to have rules recognized by the national legislation formation system, preferably in the form of a Supreme Court Regulation or Government Regulation. The results of the study show that the percentage of women's and children's rights in religious courts has a very low percentage, so it is necessary for judges to use their ex officio rights massively for the optimal fulfillment of women's and children's rights. In addition, the position of the SEMA which is considered to be a guideline or policy and does not have strong binding power, it is necessary to have rules recognized by the national legislation formation system, preferably in the form of a Supreme Court Regulation or Government Regulation. The results of the study show that the percentage of women's and children's rights in religious courts has a very low percentage, so it is necessary for judges to use their ex officio rights massively for the optimal fulfillment of women's and children's rights. In addition, the position of the Sema which is considered to be a guideline or policy and does not have strong binding power, it is necessary to have rules recognized by the national legislation formation system, preferably in the form of a Supreme Court Regulation or Government Regulation.